Philippine confluence : Iberian, Chinese and Islamic currents, c. 1500-1800 - Lopez, Ariel (Global Connections: Routes and Roots Ser., 2020)
Situated at the crossroads of the Indian and Pacific Oceans, the Spanish Philippines offer historians an intriguing middle ground of connected histories that raises fundamental new questions about conventional ethnic, regional and religious identities. This volume adds a new global perspective to the history of the Philippines by juxtaposing Iberian, Chinese and Islamic perspectives. By navigating various underexplored archival resources, senior and junior scholars from Asia, Europe and the Americas explore the diverse cultural, religious, and economic flows that shaped the early modern Philippine milieu. By zooming in from the global to the local, this book offers eleven fascinating Philippine case studies of early modern globalization.